Addressing Stem Cell Therapeutic Approaches in Pathobiology of Diabetes and Its Complications. (25th June 2018) - Peng, Bou-Yue; Dubey, Navneet Kumar; Mishra, Viraj Krishna; Tsai, Feng-Chou; Dubey, Rajni; Deng, Win-Ping; Wei, Hong-Jian
Abstract : High morbidity and mortality of diabetes mellitus (DM) throughout the human population is a serious threat which needs to be addressed cautiously. Type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) are most prevalent forms. Disruption in insulin regulation and resistance leads to increased formation and accumulation of advanced end products (AGEs), which further enhance oxidative and nitrosative stress leading to microvascular (retinopathy, neuropathy, and nephropathy) and macrovascular complications. These complications affect the normal function of organ and tissues and may cause life-threatening disorders, if hyperglycemia persists and improperly controlled. Current and traditional treatment procedures are only focused on to regulate the insulin level and do not cure the diabetic complications. Pancreatic transplantation seemed a viable alternative; however, it is limited due to lack of donors. Cell-based therapy such as stem cells is considered as a promising therapeutic agent against DM and diabetic complications owing to their multilineage differentiation and regeneration potential. Previous studies have demonstrated the various impacts of both pluripotent and multipotent stem cells on DM and its micro- and macrovascular complications. Therefore, this review summarizes the potential of stem cells to treat DM and its related complications.